HAJJ FUND INVESTMENT DEVELOPMENT STRATEGY SHARIA INVESTMENT MANAGEMENT PERSPECTIVE - Sulistyowati Sulistyowati (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The management of hajj funds in Indonesia has grown rapidly through various strategies. This study will discuss the implementation of Hajj fund investment based on a review of sharia investment management. 65% of the total funds have been invested in the Islamic banking sector, and the remaining 35% is for the Indonesian Hajj fund Sukuk. In addition to these two sectors, BPKH is also increasing Investment in other instruments such as gold Investment, direct Investment, corporate Sukuk, and different types of Investment. This type of research is qualitative with a field approach (field research). The data sources of this study were obtained from primary and secondary data with data collection techniques through participatory observation, interviews, and documentation. This research's analytical method is descriptive analysis from the perspective of Islamic investment management. The results showed that the Investment of Hajj funds did not conflict with the religion of Islam. It must be free from GHARIM, namely gharar, usury, maysir, and other prohibitions on Islamic economic transactions. In addition, it can provide benefits in the form of returns that can increase the people's use, especially the improvement of facilities and infrastructure services for prospective Indonesian pilgrims.